2013
DOI: 10.1146/annurev-earth-050212-124007
|View full text |Cite
|
Sign up to set email alerts
|

Composition and State of the Core

Abstract: The composition and state of Earth's core, located deeper than 2,900 km from the surface, remain largely uncertain. Recent static experiments on iron and alloys performed up to inner core pressure and temperature conditions have revealed phase relations and properties of core materials. These mineral physics constraints, combined with theoretical calculations, continue to improve our understanding of the core, in particular the crystal structure of the inner core and the chemical composition, thermal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
251
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 285 publications
(264 citation statements)
references
References 204 publications
8
251
0
Order By: Relevance
“…Figure 3 shows predicted inner core age and CMB temperature (T 3.5Ga ) and CMB heat flow (Q 3.5Ga ) at 3.5 Ga, the time of the earliest paleomagnetic measurement 1 . The influence of radiogenic heating is demonstrated by adding 300 ppm of 40 K at the present day, which likely represents an extreme scenario 44,63 . The shaded temperature range of 4150 ± 150 K corresponds to present estimates of the lower mantle solidus temperature 67 ; core temperatures exceeding this range suggest partial melting in past.…”
Section: Geophysical Implications Of Revised Core Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Figure 3 shows predicted inner core age and CMB temperature (T 3.5Ga ) and CMB heat flow (Q 3.5Ga ) at 3.5 Ga, the time of the earliest paleomagnetic measurement 1 . The influence of radiogenic heating is demonstrated by adding 300 ppm of 40 K at the present day, which likely represents an extreme scenario 44,63 . The shaded temperature range of 4150 ± 150 K corresponds to present estimates of the lower mantle solidus temperature 67 ; core temperatures exceeding this range suggest partial melting in past.…”
Section: Geophysical Implications Of Revised Core Propertiesmentioning
confidence: 96%
“…however, recent experiments found that adding up to 10% of Ni does not change the hexagonal close-packed crystal structure of the solid 42 , while ab initio calculations suggest that at high T the seismic properties of Fe-Ni alloys are almost indistinguishable from those of pure iron 43 . Recent studies of core composition [44][45][46] given in section 1 of Table 1; each model is named after the corresponding molar concentration.…”
Section: Materials Properties For Earth's Corementioning
confidence: 99%
“…Unfortunately, large discrepancies exist between the different studies on the topic Cao and Romanowicz, 2004;Koper and Dombrovskaya, 2005;Hirose et al, 2013, for a review) and the uncertainty in this key parameter directly affects the compositional energy. In this paper, I choose to use the value from Masters and Gubbins (2003) (see table 2) because it derives from a normal mode analysis and is therefore more likely to represent a global estimate, compared to wave reflection studies that can be influenced by the local interface state at the ICB.…”
Section: Parametermentioning
confidence: 99%
“…A recent (upward) revision in the rate of inner-core growth (e.g. Hirose et al, 2013) lowers the required viscosity, but not by more than a factor of four. Consequently, the viscosity needed to produce crystal alignment may be too large to favor viscous flow as the primary relaxation mechanism.…”
Section: Comparison With Viscous Relaxation Timementioning
confidence: 99%